Influence of the Polymer Structure and its Crystallization on the Interface Resistance in Polymer-LATP and Polymer-LLZO Hybrid Electrolytes. Issue 11 (1st November 2022) - Trevisanello, Enrico; Ates, Tugce; Passerini, Stefano; Richter, Felix H.; Janek, Jürgen
Abstract : For many years, composite electrolytes (CEs) consisting of a mixture of inorganic solid electrolytes (ISEs) and polymer electrolytes (PEs) have been investigated as promising materials for the scalable production of solid-state batteries (SSBs). It is believed that CEs can overcome limitations of the single components, namely the low room-temperature conductivity and lithium ion transference number of PEs and the poor mechanical properties and high temperature processing necessary for ISE ceramics. To facilitate ion transport in the CE between the electrodes a low and stable charge transfer resistance between PEs and ISEs is required. In this study, we investigate by means of electrochemical impedance spectroscopy (EIS) how polymer crystallinity influences the charge-transfer resistance of hetero-ionic interfaces between polyethylene oxide (PEO)-based electrolytes and Li1.5 Al0.5 Ti1.5 (PO4 )3 (LATP) as well as Li6.25 Al0.25 La3 Zr2 O12 (LLZO) as ISEs. Crystallization of PEO based electrolytes below their melting temperature leads to an increased charge-transfer resistance. On the other hand, electrolytes based on the amorphous poly[2-(2-(2-methoxyethoxy)ethoxy)ethyl glycidyl ether (PTG) do not show an increased charge transfer resistance. Finally, the conductivity of ISE-rich CEs is measured as a function of their temperature and composition for elucidating how the interface resistance influences charge transport in ISE-rich composite electrolytes.